Explaining Revisit Intention in Culinary Tourism: Case Study of Pekalongan, City of Batik - Yulius, Kevin Gustian; Franky Nilson Sudirman; Theovanus (Samarinda State Polytechnic, 2024)
Culinary tourism has become an important sector of the global tourism industry, offering destinations the opportunity to showcase their cultural identity through food. Pekalongan, a city renowned for its batik heritage, also possesses a rich culinary tradition that reflects its unique cultural identity. Despite its potential, Pekalongan has faced challenges in sustaining its tourism industry, highlighting the need to explore factors that encourage tourists to return. This study investigates the influence of seven factors—Attitude, Emotional Value, Local Food & Beverage Image, Health Value, Prestige Value, Price Value, and Taste/Quality Value—on revisit intention among urban tourists. Using a quantitative, non-experimental design, data were collected from 176 respondents through structured questionnaires and analyzed using multiple regression analysis. The findings reveal that Emotional Value and Taste/Quality Value significantly influence revisit intention, underscoring the importance of emotional connections and high-quality food in motivating repeat visits. Other factors, such as Attitude, Local Food & Beverage Image, and Price Value, contributed to the overall tourist experience but did not independently predict revisit intention. These results suggest that Pekalongan should prioritize strategies that enhance tourists’ emotional engagement and ensure consistent food quality to foster loyalty and increase revisit rates. The study contributes to the understanding of culinary tourism dynamics in smaller cities and provides actionable insights for stakeholders aiming to revitalize tourism through authentic and memorable culinary experiences. Future research should explore additional factors influencing revisit intention and their interactions to provide a more comprehensive understanding of tourist behavior.